Avaliação de famílias de meio-irmãos de duas populações de maxixe - Dantas, Jarina Idália Avelino (2014)
The Gherkin (Cucumis anguria L.) is a very common cucurbit but still underutilized in the Brazilian north-northeast. This study aimed to evaluate the genetic potential of two populations of gherkin with germplasm obtained from small farms. Hundred families half-sibs of MCE-20 (fruit with spikes) and MSE-03 (fruit without spikes) populations were evaluated in design in randomized blocks with three replications for the traits fruit weight, number of fruits per plant, longitudinal diameter, transverse diameter, format index, and soluble solids. Both populations have the potential for breeding programs to obtain plants with large fruit (> 90 g) and prolific plants. Indirect selection based on the selection of plants with higher number of fruits per plant is efficient for the selection of families with large fruit, long fruit (IF> 1.3) and prolific plants